Bone Loss Prevention of Bisphosphonates in Patients with Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis - Yan Hu; Xiaoting Chen; Xiaojing Chen; Shuang Zhang; Tianyan Jiang; Jing Chang; Yanhong Gao (Canadian Journal of Gastroenterology and Hepatology)
Objective. The purpose of this study was to evaluate the effect of bisphosphonates in improving bone mineral density (BMD) and decreasing the occurrence rate of fractures and adverse events in patients with inflammatory bowel disease (IBD). Methods. Randomized controlled trials (RCTs) which use bisphosphonates in IBD patients were identified in PubMed, MEDLINE database, EMBASE database, Web of Knowledge, and the Cochrane Databases between 1990 and June 2016. People received bisphosphonate or placebos with a follow-up of at least one year were also considered. STATA 12.0 software was used for the meta-analysis. Results. Eleven randomized clinical trials were included in the meta-analysis. The data indicated that the percentage change in the increased BMD in the bisphosphonates groups was superior to that of the control groups at the lumbar spine and total hip. At the femoral neck, there was no significant difference between the two groups. The incidence of new fractures during follow-up showed significant reduction. The adverse event analysis revealed no significant difference between the two groups. Conclusion. Our results demonstrate that bisphosphonates therapy has an effect on bone loss in patients with IBD but show no evident efficiency at increasing the incidence of adverse events.